How do palliative care doctors recognise imminently dying patients? A judgement analysis. Issue 11 (25th November 2018) - White, Nicola; Harries, Priscilla; Harris, Adam JL; Vickerstaff, Victoria; Lodge, Philip; McGowan, Catherine; Minton, Ollie; Tomlinson, Christopher; Tookman, Adrian; Reid, Fiona; Stone, Patrick
Abstract : Objectives: To identify a group of palliative care doctors who perform well on a prognostic test and to understand how they make their survival predictions. Design: Prospective observational study and two cross-sectional online studies. Setting: Phase I: an online prognostic test, developed from a prospective observational study of patients referred to palliative care. Phase II: an online judgement task consisting of 50 hypothetical vignettes. Participants: All members of the Association of Palliative Medicine (APM) were eligible (n=~1100). 99 doctors completed the prognostic test and were included in the phase I analysis. The top 20% were invited to participate in phase II; 14/19 doctors completed the judgement task and were included in the phase II analysis. Measures: Phase I: participants were asked to give a probability of death within 72 hours (0%–100%) for all 20 cases. Accuracy on the prognostic test was measured with the Brier score which was used to identify the 'expert' group (scale range: 0 (expert)–1 (non-expert)). Phase II: participants gave a probability of death within 72 hours (0%–100%). A mixed model regression analysis was completed using the percentage estimate as the outcome and the patient information included in the vignettes as the predictors. Results: The mean Brier score of all participants was 0.237 (95% CI 0.235 to 0.239). The mean Brier score of the 'experts' was 0.184 (95% CI 0.176 to 0.192). Six of the seven prognostic variables included in the hypothetical vignettes were significantly associated with clinician predictions of death. The Palliative Performance Score was identified as being the most influential in the doctors' prognostic decision making (β=0.48, p<0.001). Conclusions: This study identified six clinical signs and symptoms which influenced the judgement policies of palliative care doctors. These results may be used to teach novice doctors how to improve their prognostic skills.